Virtual Element Method for fourth order problems: L2-estimates. (October 2016) - Chinosi, Claudia; Marini, L. Donatella
Abstract: We analyse the family of C 1 -Virtual Elements introduced in Brezzi and Marini (2013) for fourth-order problems and prove optimal estimates in L 2 and in H 1 via classical duality arguments.